Implementation of an opioid weaning protocol to improve pain management, and to prevent or decrease iatrogenic withdrawal syndrome in the neonatal intensive care. Issue 3 (September 2019) - Muirhead, Renee; Kynoch, Kathryn
ABSTRACT: Aim: The aim of this evidence implementation project was to improve pain assessment and management of the neonate receiving an opioid infusion, and to prevent or decrease the incidence of iatrogenic withdrawal syndrome (IWS). Methods: The current project was carried out in two intensive care areas of a 79 bed tertiary Neonatal Unit in Australia. A pre/postaudit design was utilized. Patient charts were reviewed to collect baseline audit data on pain assessments and titration of opioids. A weaning protocol was developed and implemented along with targeted staff education to align current practice with best practice recommendations. A postimplementation audit was then conducted to evaluate changes in practice. Results: A total of 32 charts (13 pre/19 post) were reviewed to evaluate pain assessment, titration of opioids, and the identification of any signs and symptoms of IWS. The results demonstrated an improvement in the completion of pain assessments by 34%, and 100% compliance to withdrawal assessment following the introduction of an IWS assessment tool. For neonates receiving analgesics for less than 4 days, adherence to the weaning schedule occurred in 75%. No clinical signs of IWS were seen in this cohort. For neonates receiving analgesics for greater than 4 days, adherence to the weaning schedule occurred in only 55%. Of those neonates where the protocol was not followed, 67% developed clinical signs of IWS. Conclusion: Although this project demonstrated improvements in pain assessment and the identification of IWS, lack of adherence to the pain management policy and weaning tool has increased awareness of the importance of collaboration within the multidisciplinary team to improve outcomes. Several barriers were identified prior to implementation and various methods were employed to overcome these. Despite this, consistency of practice and change-management remain a challenge in clinical care.